GS Barbershop Service Management System - Ibrahim, Ahmad Irsyaduddin; Hasan Basari, Abd Samad (Applied Information Technology And Computer Science, 2025)
The GS Barbershop, located in Taman Cempaka Serom and operational since 2020, offers various grooming services such as haircuts, beard trims, and hair treatments, catering to men and children. However, the barbershop faces challenges with manual processes for appointment bookings, leading to long wait times, scheduling conflicts, and a lack of systematic customer management. These issues influence operational efficiency and affect customer satisfaction. This project aims to design, develop, and test a GS Barbershop Service Management System to streamline operations and enhance customer experience. The system will include modules for login and registration, appointment booking and management, barber availability, payments, reports, and service management, catering to key users such as administrators, barbers, and customers. The prototyping methodology is chosen as it enables the creation of an initial model for users to interact with before the final system is developed. The system will also improve transparency in appointment handling, reduce no-shows through email reminders, and enhance the barbershop’s financial reliability via a deposit payment feature. Data analysis shows that the GS Barbershop Service Management System can improve appointment scheduling efficiency, reduce errors, and enhance communication between customers and staff. A significant finding is the need for an integrated system to ensure smooth operations and better customer experience. These findings indicate that a structured system can elevate barbershop operations and improve overall customer satisfaction. Future studies could focus on integrating advanced technologies like data analytics to provide insights into customer preferences and further enhance service delivery.